2002
DOI: 10.1177/0810387
|View full text |Cite
|
Sign up to set email alerts
|

Noggin Blocks Osteoinductive Activity of Porcine Enamel Extracts

Abstract: Enamel extracts induce biomineralization such as osteogenesis and cementogenesis, but the molecular component responsible for this activity remains uncertain. We fractionated enamel extracts from developing pig teeth and isolated the osteoinductive fraction. Proteins from pig enamel scrapings were extracted under alkaline conditions (pH 10.8) and fractionated with the use of a Sephadex G-100 (size exclusion) column. The ability of each fraction to enhance alkaline phosphatase (ALP) activity was assayed in ST2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 31 publications
4
33
0
Order By: Relevance
“…The medium was replaced every 3 days. On the 21 st and 28 th day, mineralized nodules were determined by the staining of alizarin red (Sigma-Aldrich, St. Louis, MO, USA) as previously described [25], [26]. Culture plates were photographed by NIS-Elements F2.20 (Nikon Eclipse 80i, Tokyo, Japan), and the calcified areas were then quantified using a software of Image-Pro Plus 6.0.…”
Section: Methodsmentioning
confidence: 99%
“…The medium was replaced every 3 days. On the 21 st and 28 th day, mineralized nodules were determined by the staining of alizarin red (Sigma-Aldrich, St. Louis, MO, USA) as previously described [25], [26]. Culture plates were photographed by NIS-Elements F2.20 (Nikon Eclipse 80i, Tokyo, Japan), and the calcified areas were then quantified using a software of Image-Pro Plus 6.0.…”
Section: Methodsmentioning
confidence: 99%
“…Although early immunoassay studies could not identify the presence of growth factors in EMD,16 nominal levels of transforming growth factor β1 have been detected immunologically 17. In addition, by using noggin, a bone morphogenic protein (BMP)-binding protein, investigators have identified BMP-2 and BMP-4 in an osteoinductive fraction of enamel extracts 18. A wide range of in vitro and in vivo studies have demonstrated that EMD and amelogenins stimulate growth of multiple mesenchymal cell types including fibroblasts, cementoblasts, osteoblasts, and stem cells 19,20.…”
Section: Composition Of Enamel Matrix Proteinsmentioning
confidence: 99%
“…Emdogain is a commercially available mixture of EMDs. The composition of EMDs has been described as a hydrophobic enamel matrix protein complex derived from 6-month-old porcine tooth buds containing more than 90% amelogenin as well as enamelin, tuftelin, tuft proteins, ameloblastin [40], and other peptides such as bone morphogenetic proteins (BMPs) and transforming growth factor-beta (TGF- β ) [41, 42]. It has been known that amelogenins are self-assembled into supermolecular aggregates, which are generated in insoluble extracellular matrix [43] with high affinity for collagens and HA [44, 45].…”
Section: Discussionmentioning
confidence: 99%